The purpose of this research was to understand the addition of SnO2 film with radius and mass material variation on resistance value of very fine particle carbon film from kerosene oil lamp combustion. This research was started by making carbon film from kerosene oil lamp soot on a glass slide. Next, carbon film was added with SnO2 nanomaterial film. SnO2 nanomaterial was produced from combustion of SnCl2.2H2O with 0,4; 0,6; 0,8; 1,0; and 1,2 cm radius variation and 0,1; 0,2; 0,3; 0,4; and 0,5 g - Fatya Kurniati; W.S. Brams Dwandaru (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
Penelitian ini bertujuan untuk i) mengetahui pengaruh variasi massa dan variasi waktu pembakaran SnCl2 terhadap nilai hambatan yang dihasilkan pada lapisan nanomaterial SnO2, ii) mengetahui pengaruh jumlah mechanical exfoliation pada variasi massa dan waktu pembakaran SnCl2 terhadap nilai hambatan yang diperoleh, iii) mengetahui pengaruh jumlah mechanical exfoliation terhadap nilai transmitansi dan hasil karakterisasi SnO2 menggunakan XRDPembuatan lapisan dilakukan menggunakan metode pemanasan (pembakaran) bahan SnCl2. Variasi yang dilakukan yakni variasi massa SnCl2 dengan massa 0,1 gram, 0,2 gram, 0,3 gram, 0,4 gram, dan 0,5 gram, dan variasi waktu pembakaran yaitu 4, 6, 8, 10, dan 12 menit. Setelah pembuatan sampel selesai, selanjutnya dilakukan uji hambatan yang dihasilkan sampel, uji hambatan dengan melakukan mechanical exfoliation (ME), dan uji transmitansi. Karakterisasi yang dilakukan adalah karakterisasi menggunakan XRD yang dilakukan ME pada sampel.Hasil penelitian menunjukkan bahwa variasi massa dan waktu pembakaran berpengaruh terhadap nilai hambatan yang dihasilkan. Semakin besar massa pembakaran yang digunakan, maka nilai hambatan akan semakin kecil. Pada variasi waktu pembakaran, semakin lama waktu yang digunakan maka semakin kecil nilai hambatan yang dihasilkan. ME memiliki pengaruh yang sama pada uji hambatan yang dilakukan, baik untuk variasi massa maupun waktu pembakaran. Semakin besar jumlah ME maka semakin besar nilai hambatannya. Pada uji transmitansi, ME tidak berpengaruh besar terhadap nilai transmitansi, nilai transmitansi rata-rata yang dihasilkan sebesar 85,58%. Pada karakterisasi menggunakan XRD, ME yang dilakukan memperlihatkan sifat kristal dari SnO2.Kata Kunci: nanomaterial, mechanical exfoliation, hambatan, SnCl2, SnO2, massa pembakaran, waktu pembakaran This research aims to understand i) the effect of variation of mass and burning time of SnCl2 against resistance values generated in the layer of nanomaterial SnO2, ii) the effect of the number of mechanical exfoliation on the variation of the mass and burning time SnCl2 against resistance values obtained, iii) the effect the number of mechanical exfoliation towards the transmittance values and characterization of SnO2 using XRD results.This study began by making the coating using a method of heating (burning) SnCl2 material. Variations were made for the mass and burning time of SnCl2. Mass variation of SnCl2 used are 0.1 grams, 0.2 grams, 0.3 grams, 0.4 grams, and 0.5 grams. The time variation of combustion used are 4, 6, 8, 10, and 12 minutes. Once the sample preparation is complete, then the resulting sample are tested by mechanical exfoliation (ME) and the transmittance test. Characterization using XRD, ME is also conducted on the samples.The results showed that the variation of mass and burning time effect the resulting resistance values. The greater the mass of combustion used the smaller. For time variation of burning, the longer the burning time, the smaller the resistance value. ME has the same effect on conducted both for variations in the mass and burning time. The greater the number of ME, the greater the resistance. In the transmittance test, ME did not effect the transmittance value, and the average transmittance values is 85.58%. On characterization using XRD, ME showed characteristics of SnO2 crystals.Keywords: nanomaterials, mechanical exfoliation, resistance, SnCl2, SnO2, mass burning, burning time